The role of natural halogens in global tropospheric ozone chemistry and budget under different 21st century climate scenarios - Badia, Alba (2021)
Tropospheric ozone ((Formula presented.)) is an important greenhouse gas and a surface pollutant. The future evolution of (Formula presented.) abundances and chemical processing are uncertain due to a changing climate, socioeconomic developments, and missing chemistry in global models. Here, we use an Earth System Model with natural halogen chemistry to investigate the changes in the (Formula presented.) budget over the 21st century following Representative Concentration Pathway (RCP)6.0 and RCP8.5 climate scenarios. Our results indicate that the global tropospheric (Formula presented.) net chemical change (NCC, chemical gross production minus destruction) will decrease (Formula presented.), notwithstanding increasing or decreasing trends in ozone production and loss. However, a wide range of surface NCC variations (from −60 (Formula presented.) to 150 (Formula presented.)) are projected over polluted regions with stringent abatements in (Formula presented.) precursor emissions. Water vapor and iodine are found to be key drivers of future tropospheric (Formula presented.) destruction, while the largest changes in (Formula presented.) production are determined by the future evolution of peroxy radicals. We show that natural halogens, currently not considered in climate models, significantly impact on the present-day and future global (Formula presented.) burden reducing (Formula presented.) 30–35 Tg (11–15 (Formula presented.)) of tropospheric ozone throughout the 21st century regardless of the RCP scenario considered. This highlights the importance of including natural halogen chemistry in climate model projections of future tropospheric ozone.